2014
DOI: 10.5799/ahinjs.02.2014.02.0126
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of extended-spectrum β-lactamases producing Enterobacteriaceae in a general hospital in Saudi Arabia

Abstract: Objective: To estimate the prevalence and associated risk factors of extended-spectrum β-lactamase producing Enterobacteriaceae (ESBL) in King Khaled General Hospital, Saudi Arabia. Methods:A twelve -month retrospective study for the presence of ESBL producing Enterobacteriaceae infection was performed by using the Microbiology and Infection Control Departments' database. For all the collected specimens, microbiological identification and antimicrobial sensitivity testing were done using MicroScan WalkAway sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
16
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 26 publications
7
16
5
Order By: Relevance
“…In addition, ESBL positivity also was not significantly associated with age (P-value=0.056) as opposed to a report by Jesus Rodriguez-Bano who found that older age in male patients (OR,1.03; 95% CI, 1.03-1.05) was a risk factor [25]. While OK Azap and Kandeel A did not find age as a risk factor (P-value=0.952 [27,14].…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…In addition, ESBL positivity also was not significantly associated with age (P-value=0.056) as opposed to a report by Jesus Rodriguez-Bano who found that older age in male patients (OR,1.03; 95% CI, 1.03-1.05) was a risk factor [25]. While OK Azap and Kandeel A did not find age as a risk factor (P-value=0.952 [27,14].…”
Section: Discussioncontrasting
confidence: 60%
“…Similar to what was observed by Kandeel. A in a study conducted in Saudi Arabia and Dong Sup Lee in Korea [10,14]. Going to malignancy, in the current study, it was not significantly associated with UTI-ESBL.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…6,27 In Saudi Arabia and Tanzania, a higher frequency of ESβL-induced UTIs was found to be hospitalacquired compared with community-acquired infections (67% and 64%, respectively). 6,28 The high frequency of ESβL, especially among community-acquired UTIs, in our study is Extended-spectrum β-lactamase isolates were extremely resistant to cefepime and amoxicillin-clavulanic acid, and susceptible to carbapenems. All ESβL E. coli isolates 19 were sensitive to fosfomycin.…”
Section: Discussionmentioning
confidence: 57%
“…High level of carbapenem resistance had been observed in one study which was 20% [10]. In another study in the central region in Saudi Arabia, 57% of ESBL-producing E. coli isolates were of community origin [11].…”
Section: Discussionmentioning
confidence: 99%